Flow Reversal in Traveling-Wave Electrokinetics: An Analysis of Forces Due to Ionic Concentration Gradients - García-Sánchez, P; Ramos, A; González, A; Green, N. G; Morgan, H (Langmuir, 2009)
Pumping of electrolytes using ac electric fields from arrays of microelectrodes is a subject of current research. The behavior of fluids at low signal amplitudes (<2−3 Vpp) is in qualitative agreement with the prediction of the ac electroosmosis theory. At higher voltages, this theory cannot account for the experimental observations. In some cases, net pumping is generated in the direction opposite to that predicted by the theory (flow reversal). In this work, we use fluorescent dyes to study the effect of ionic concentration gradients generated by Faradaic currents. We also evaluate the influence of factors such as the channel height and microelectrode array shape in the pumping of electrolytes with traveling-wave potentials. Induced charge beyond the Debye length is postulated to be responsible for the forces generating the observed flows at higher voltages. Numerical calculations are performed in order to illustrate the mechanisms that might be responsible for generating the flow.